Influence of Root Diameter and Soil Depth on the Xylem Anatomy of Fine- to Medium-Sized Roots of Mature Beech Trees in the Top- and Subsoil - Kirfel, Kristina; Leuschner, Christoph; Hertel, Dietrich; Schuldt, Bernhard (Frontiers in Plant Science, 2017)
Despite their importance for water uptake and transport, the xylem anatomical and hydraulic properties of tree roots have only rarely been studied in the field. We measured mean vessel diameter (D), vessel density (VD), relative vessel lumen area (lumen area per xylem area) and derived potential hydraulic conductivity (Kp) in the xylem of 197 fine- to medium-diameter roots (1–10 mm) in the topsoil and subsoil (0–200 cm) of a mature European beech forest on sandy soil for examining the influence of root diameter and soil depth on xylem anatomical and derived hydraulic traits. All anatomical and functional traits showed strong dependence on root diameter and thus root age but no significant relation to soil depth. Averaged over topsoil and deep soil and variable flow path lengths in the roots, D increased linearly with root diameter from ∼50 μm in the smallest diameter class (1–2 mm) to ∼70 μm in 6–7 mm roots (corresponding to a mean root age of ∼12 years), but remained invariant in roots >7 mm. D never exceeded ∼82 μm in the 1–10 mm roots, probably in order to control the risk of frost- or drought-induced cavitation. This pattern was overlain by a high variability in xylem anatomy among similar-sized roots with Kp showing a higher variance component within than between root diameter classes. With 8% of the roots exceeding average Kp in their diameter class by 50–700%, we obtained evidence of the existence of ‘high-conductivity roots’ indicating functional differentiation among similar-sized roots. We conclude that the hydraulic properties of small to medium diameter roots of beech are mainly determined by root age, rendering root diameter a suitable predictor of hydraulic functioning, while soil depth – without referring to path length – had a negligible effect.